في الفئران المختبرية ودراسة التغيرات النسجية المصاحبة لها Echinococcus granulosus استزراع الاكياس العدرية لطفيلي المشوكة الحبيبية - عذراء عبد الامير عزيز الحلفي (University of Thi-Qar Journal of Science, 2019)
This study was carried out to follow liability of transporting hydatid cyst among mice ,Cysts isolated from mice labture infected by protoscolex after four month ,and thensurgically transpored to uninfected mice. After one month post cultivation the cyst formingtwo laminated layer ,one of this developed and the other is still in the beginning ofdevelopment in addition to germinal layer which consist of more row of cells, Controlanimals had cysts formed from one laminated layer and one row of germ layer.Thehistological changes in cultivated animals were less sever than animals infected withprotoscolex